1980
DOI: 10.1037/0022-0167.27.6.620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of profane language and physical attractiveness on perceptions of counselor behavior.

Abstract: The effects of counselor profanity and physical attractiveness for male and female counselors were examined in a counseling analogue. In a 2 X 2 X 2 factorial design, 72 male and female volunteer subjects were randomly assigned to one of eight experimental conditions of videotaped counseling sessions where they rated the counselor on a variety of dependent measures related to their impressions of counselor professional and personal attributes, likelihood of counseling for a variety of presenting problems, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 9 publications
2
28
0
Order By: Relevance
“…For instance, photos of attractive teachers tend to be rated more positively on dimensions such as warmth, instructive ability, and communication ability (Goebel & Cashen, 1979;Lombard0 & Tocci, 1979), although there is some evidence that providing additional information, such as teaching style, may reduce or eliminate this effect (Buck & Tiene, 1989). Numerous studies have also found that photos of attractive counselors are rated more favorably than unattractive counselors, although providing subjects with demographic or personal disclosures by the counselor again attenuates the effect (Cash, Begley, McCown, & Weise, 1975;Cash & Kehr, 1978;Cash & Salzbach, 1978;Lewis & Walsh, 1978; Paradise, Cohl, & Zweig, 1980).…”
Section: Attractivenessmentioning
confidence: 99%
“…For instance, photos of attractive teachers tend to be rated more positively on dimensions such as warmth, instructive ability, and communication ability (Goebel & Cashen, 1979;Lombard0 & Tocci, 1979), although there is some evidence that providing additional information, such as teaching style, may reduce or eliminate this effect (Buck & Tiene, 1989). Numerous studies have also found that photos of attractive counselors are rated more favorably than unattractive counselors, although providing subjects with demographic or personal disclosures by the counselor again attenuates the effect (Cash, Begley, McCown, & Weise, 1975;Cash & Kehr, 1978;Cash & Salzbach, 1978;Lewis & Walsh, 1978; Paradise, Cohl, & Zweig, 1980).…”
Section: Attractivenessmentioning
confidence: 99%
“…In 6 studies higher ratings of counselor attractiveness were found for the following variables (again with the positively related descriptor in parentheses): counselor sexual preference (gay; , sex role orientation (egalitarian; Atkinson & Alpert, 1981), ethnicity (Black; Green, Cunningham, & Yanico, 1986;Paurohit et al, 1982), physical attractiveness (attractive; Green et al, 1986;Paradise et al, 1980), and obvious physical disability (disabled; Mallinckrodt & Helms, 1986). Five studies did not find a relationship between the subjects' ratings of counselor attractiveness and counselor characteristics of weight (McKee & Smouse, 1983), physical disability (Strohmer & Biggs, 1983), informal attire (Roll & Roll, 1984), age (Schneider & Hayslip, 1986), and gender (Angle & Goodyear, 1984).…”
Section: Attractivenessmentioning
confidence: 99%
“…Other studies that have examined verbal behaviors such as interpretation techniques (Milne & Dowd, 1983) or paradoxical versus nonparadoxical directives (Perrin & Dowd, 1986) have not found significant relationships with perceived attractiveness; the use of profanity, however, did lower ratings of perceived counselor attractiveness (Paradise, Cohl, & Zweig, 1980).…”
mentioning
confidence: 99%
“…Therapist attractiveness may have an even greater influence on the client's expectations of effective therapy than the therapist's skill level (Vargas & Borkowski, 1982). Although clients might consider other variables, such as gender or use of a specific technique, to be important determinants of a therapist's effectiveness, attractiveness has greater influence on clients' favorable perception of a therapist's personal and professional characteristics (Cash & Kehr, 1978;Paradise, Cohl, & Zweig, 1980).…”
mentioning
confidence: 99%